A comparative assessment of the L1 and L2 reading performance of Grade 7 learners in English - Manyike, Tintswalo V.; Lemmer, Eleanor (Per Linguam : A Journal of Language Learning, 2008)
The role of English and the indigenous languages in South African schooling is highly contested. Research endorses the mother tongue (L1) as the most appropriate language of learning and teaching (LoLT) and the basis for the addition of a second language (L2). However, in South Africa English is the preferred LoLT and English proficiency is integral to academic achievement. This article reports on an investigation of Grade 7 Xitsonga-speaking learners’ reading performance in English and in Xitsonga. Based on a study of the literature on the link between language proficiency and academic success, an empirical inquiry assessed the reading performance of grade 7 Xitsonga-speaking learners using a standardised test in English and in Xitsonga. Learners’ reading performance in both Xitsonga, their L1, and English, their LoLT since grade 4, was poor.